Separate Saccharification and Fermentation for Bioethanol Production from Raw Seaweed Sargassum sp. - Aulia Rachmayanti; R. Marwita Sari Putri; Aidil Fadli Ilhamdy (Marinade, 2019)
The purpose of this study to obtain the best reducing sugars using acid solvent H2SO4 and HCl to be used as a substrate in fermentation processes to produce bioethanol. The research phase includes the preparation of raw materials Sargassum sp., the processing of acid hydrolysis used a solvent H2SO4 and HCl. Hydrolysis then fermented for five days for the production of etanol. Hydrolysis using acid solvent H2SO4 obtained the best acid concentration of 2% with the result of reducing sugars 82,62 g/L, whereas using HCl acid solvent obtained the best acid concentration of 2% with the result of reducing sugars 74,79 g/L. Fermented for 120 hours to produce ethanol each H2SO4 2 ml and 3 ml HCl.